Prioritising challenges and actions for freshwater conservation in a tropical biodiversity hotspot - Alexandra, Zieritz; Christopher, Gibbins; Yixiong, Cai; Farah, Diba; Lydia X., Gan; Manuel, Lopes-Lima; Jose Christopher, E. Mendoza; John, Morse; Ting, Hui Ng; Elysia X.P., Toh; John, Pfeiffer; Bi, Wei Low; et al. (Elsevier Ltd., 2024)
Tropical fresh waters experience one of the highest rates of biodiversity loss globally. Effective tropical freshwater biodiversity conservation requires prioritised and concerted action that is informed by science, but efforts to synthesise the available expertise and knowledge remain lacking to date. Here, we identify the most important challenges for freshwater conservation in the tropical biodiversity hotspot Sundaland, and provide roadmaps towards addressing them. A Delphi technique for consensus building, adopted across a panel of 18 experts, identified challenges under the categories of threats, research needs, and social and policy-related challenges. Threats were ranked by their importance in terms of the spatial extent, severity and persistence, while research needs, and social and policy-related challenges were ranked according to how severely they impede conservation. The top-ranked challenges were (1) threats: deforestation, agriculture, urbanisation, water management; (2) research needs: lack of data on freshwater biodiversity, systematic biology, understanding multiple stressors and resilience of freshwater ecosystems; and (3) social and policy-related challenges: low priority of freshwater biodiversity, lack of expertise, lack of systematic conservation planning, and growth of population and affluence. Addressing these challenges requires an approach that integrates improved communication and collaboration among researchers and stakeholders, scientific outreach to improve public appreciation of freshwater biodiversity and build capacity, implementation of best practices to mitigate negative human impacts, systematic conservation planning, and adoption of novel tools and technologies to address important knowledge gaps. This work can serve as a model for prioritising conservation actions in other regions that lose biodiversity at similarly rapid rates.